Panel IV: The Appropriations Power and the Necessary and Proper Clause - Edwin Meese III; William Barr; Louis Fisher; Geoffrey P. Miller; Kate Stith (Washington University Law Quarterly, 1990)
We are going to talk about some of the coercive aspects that the Constitution, in a sense, gives to the Congress, because there are some constitutional powers given to the Congress which directly relate to how the executive branch does its job.